180 | ÷ | x | + | 90 | ÷ | ( | x | + | 12 | ) | = | 1 |
Multiply both sides of the equation by: | x |
180 | + | 90 | ÷ | ( | x | + | 12 | ) | × | x | = | 1 | x |
Multiply both sides of the equation by: | ( | x | + | 12 | ) |
180 | ( | x | + | 12 | ) | + | 90 | x | = | 1 | x | ( | x | + | 12 | ) |
180 | x | + | 180 | × | 12 | + | 90 | x | = | 1 | x | ( | x | + | 12 | ) |
180 | x | + | 180 | × | 12 | + | 90 | x | = | 1 | x | x | + | 1 | x | × | 12 |
180 | x | + | 2160 | + | 90 | x | = | 1 | x | x | + | 12 | x |
270 | x | + | 2160 | = | 1 | x | x | + | 12 | x |